Get started with Gouache : a colorful guide to painting the world around you - Block, Emma (Watson-Gutill, 2020)
"Description: The Art of Painting with Gouache is a complete guide to using the medium. It includes a history and overview as well as information on techniques, color theory, and the best materials to use for painting. Block also gives us 30 practice lessons from beginning level to advanced that build upon the techniques she presents"--